A polymer, oral mucosal adhesive patch and its preparation method and use

By using specific block monomers in oral mucosal adhesion patches to synthesize polymers through free radical polymerization, the problems of insufficient adhesion and short drug retention time in the prior art of oral mucosal disease are solved, more effective treatment effects are achieved, and the bioavailability of drugs is improved.

CN119331163BActive Publication Date: 2025-03-28SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411883463.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing local therapeutic agents for oral mucosal diseases do not have enough adhesion in a humid environment and the drug retention time is short, resulting in poor clinical efficacy.

Method used

A polymer synthesized by free radical polymerization of block monomers such as methacrylic acid, methacrylamide, 1-(methacryloxy)pyrrolidine-2,5-dione, (3-acrylamide propyl)trimethylammonium chloride and 2-(2-(2-(3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethylacrylate was prepared by radical polymerization.

Benefits of technology

This adhesion patch exhibits excellent adhesion and drug release performance in a wet oral environment. Its adhesion is better than that of commercially available oral patches. The adhesion time in the body is longer than that of drug molecules, which can significantly alleviate the lesions of the tongue and enter the blood circulation throughout the body through the oral submucosal blood vessels, improving the bioavailability of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331163B_ABST
    Figure CN119331163B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of medical technology, and specifically relates to a polymer, an oral mucosal adhesive patch, and a preparation method and use thereof. The present invention provides an oral mucosal adhesive patch based on a polymer. By optimizing the monomer ratio of the polymer, a polymer is prepared, and the polymer is prepared into an oral mucosal adhesive patch. The adhesive patch has excellent mucosal wet adhesion performance, and the wet adhesion force and adhesion time are better than those of commercially available oral patches and drugs; the porous structure is conducive to carrying drugs; the neutral surface is non-irritating to oral adhesion; it gradually disintegrates in a saliva environment, and is suitable for highly dynamic and humid special environments. When the adhesive patch is used to treat oral leukoplakia in rats, the loaded drug can significantly alleviate the lesions on the tongue. Furthermore, the drug delivered by the adhesive patch through the oral mucosa can also enter the systemic blood circulation through the oral submucosal blood vessels, thereby achieving efficient treatment of systemic diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to an oral mucosal adhesive patch and a preparation method and use thereof. Background Art

[0002] The oral cavity is the beginning of the digestive tract and has a special environment that is open, highly dynamic, moist, and bacterial. The oral mucosa refers to the moist lining in the oral cavity, the surface of which is covered by a continuous gel layer formed by mucus. Oral mucosal diseases are a general term for a wide variety of diseases of various types that occur on the oral mucosa, manifested as changes in the color, shape, texture, and function of the oral mucosa, often accompanied by obvious pain, swelling, and other discomfort. Representative oral mucosal diseases include recurrent aphthous ulcers, oral leukoplakia, and oral lichen planus. Most oral mucosal diseases have complex causes, long courses of disease, and chronic lesions. Most of them will have erosions or ulcers, and some cases may also develop cancer. In addition, some oral mucosal diseases, such as oral candidiasis and proliferative suppurative stomatitis, are closely related to systemic diseases, including various immune system and digestive system diseases such as AIDS, malignant tumors, and inflammatory bowel disease. Since oral mucosal lesions are superficial and easy to observe, topical drug therapy is an important or even the first choice for their treatment. The dosage forms of topical drug therapy include gargles, patches, gels, ointments, etc. However, due to the small total surface area of ​​the oral mucosa (only about 200 cm 2 ), continuous saliva secretion causes the drug to be diluted and flushed, and physiological activities such as chewing cause the drug to dissolve and be lost. In addition, the complex and special environment of the oral cavity makes the local effective drug dose of oral mucosal lesions low and the drug retention time short, which ultimately leads to poor clinical efficacy of local treatment. Therefore, it is urgent to develop excellent preparations suitable for the moist environment of the oral cavity to achieve effective treatment of oral mucosal diseases.

[0003] The oral patch is a thin-film drug delivery system, which is a convenient and effective local treatment for oral mucosal diseases. The ideal oral patch should have good mucosal adhesion and drug release properties. The research progress of oral patches is mainly focused on improving their adhesion properties, drug release behavior and bioavailability. For example, researchers have developed an oral patch with strong wet adhesion properties by imitating the wet adhesion properties of mussels. This patch exhibits excellent adhesion and drug release properties in a moist oral environment, solving the problem of insufficient adhesion of traditional oral mucosal topical preparations in a moist environment. However, mussel-mimicking polymers have problems such as easy oxidation and poor wet adhesion to the mucosa.

[0004] In summary, the current drug preparations for the treatment of oral mucosal diseases in clinical practice have problems such as poor wet adhesion to the oral mucosa, short local retention time of the drug in the oral mucosa, and poor clinical efficacy. Summary of the invention

[0005] In view of the problems of the prior art, the present invention provides an oral mucosal adhesive patch and a preparation method and use thereof.

[0006] The present invention provides a polymer, which is prepared according to the following steps: mixing block A, block B, and block C, and reacting to obtain a polymer;

[0007] The block A is selected from one or a combination of at least two of methacrylic acid, methacrylamide, and 1-(methacryloyloxy)pyrrolidine-2,5-dione; the block B is selected from at least one of (3-acrylamidopropyl)trimethylammonium chloride, (4-(acryloyloxy)butyl)amino)(amino)methaniminium, 2,2,2-trifluoroacetate; the block C is selected from at least one of 2-(2-(2-((3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethylacrylate, and 2-[2-(2-{[3-(2,4,6-trioxo-1,3,5-triazinan-1-yl)propanoyl]oxy}ethoxy)ethoxy]ethylprop-2-enoate;

[0008] The molar content ratio of the block A, block B and block C is 21.25%-71.25%: 21.25%-71.25%: 5%-15%.

[0009] Preferably, the molar content ratio of block A, block B and block C is 45%:45%:10%.

[0010] Preferably, the mixing is mixing block A, block B, block C and an initiator;

[0011] The initiator is selected from 2,2′-azobis[2-(2-imidazoline-2-yl)propane)] dihydrochloride and N,N-diisopropylethylamine.

[0012] Preferably, the mixed solvent is selected from water and dichloromethane; and / or the reaction temperature is 65-70° C.; and / or the reaction speed is 400-500 rpm; and / or the reaction time is 1.5-2 hours.

[0013] The present invention provides a method for preparing any of the above-mentioned polymers, comprising the following steps: mixing block A, block B and block C, and reacting to obtain the polymer.

[0014] The present invention provides use of any of the above polymers for drug delivery and / or wet adhesives and / or preparation of medical patches.

[0015] The present invention provides an oral mucosal adhesive patch, which is prepared according to the following steps: pressing any one of the above-mentioned polymers into a sheet to obtain the oral mucosal adhesive patch.

[0016] Preferably, after being pressed into tablets, a hydrophobic layer is added to one side of the tablets.

[0017] The present invention provides a method for preparing any one of the above-mentioned oral mucosal adhesive patches, comprising the following steps: pressing any one of the above-mentioned polymers into sheets to obtain.

[0018] The present invention provides the use of any one of the above-mentioned oral mucosal adhesive patches for drug delivery;

[0019] And / or, use in preparing materials for treating oral mucosal diseases or tissue repair materials.

[0020] The present invention uses methacrylic acid / methacrylamide / 1-(methacryloyloxy)pyrrolidine-2,5-dione, (3-acrylamidopropyl)trimethylammonium chloride / guanidine, and base / cyanuric acid derivatives as basic building units, synthesizes 12 copolymers through free radical polymerization, and forms 12 oral adhesive patches with different compositions by tableting the polymer powder. The adhesive patch has good mucosal wet adhesion performance, better adhesion than commercially available oral patches, and longer in vivo adhesion time than drug molecules. The porous structure of the adhesive patch is conducive to drug loading, and the neutral patch surface has no obvious stimulation to oral adhesion. In the oral saliva environment, the adhesive patch will gradually disintegrate, and is suitable for the highly dynamic and moist special environment of the oral cavity. The adhesive patch has good biocompatibility. When used to treat oral leukoplakia (OLK) in rats, the loaded drug can significantly alleviate the lesions of the tongue. Compared with applying drugs alone or applying adhesive patches alone, drug-loaded adhesive patches can achieve more effective treatment effects and meet the needs of treating oral mucosal diseases. Furthermore, the drugs delivered by the adhesive patch through the oral mucosa can also enter the systemic blood circulation through the oral submucosal blood vessels, thereby improving the bioavailability of the drugs and achieving efficient treatment of systemic diseases.

[0021] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0022] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a picture of the copolymer powder and the oral mucosal adhesive patch prepared therefrom.

[0024] Figure 2 is the H NMR spectrum of the copolymer p(MPA-co-APTAC-co-NA) 1 H NMR) diagram.

[0025] Figure 3 This is the ultraviolet-visible absorption spectrum (UV-vis) of the copolymer p(MPA-co-APTAC-co-NA).

[0026] Figure 4 This is a diagram showing the adhesion effect of the adhesive patch on different tissues.

[0027] Figure 5 Figure A is the adhesion result of the adhesive patch prepared at different TGA-NA ratios, Figure B is the adhesion result of the adhesive patch prepared at different MPA:APTAC ratios, Figure C is the adhesion result of the adhesive patch to wet and dry surfaces, Figure D is the adhesion result of the adhesive patch under different pressures, Figure E is the adhesion result of different oral patches, Figure F is the adhesion result of the adhesive patch obtained by different test methods, Figure G is a field picture of the adhesion measured by the lap shear method, Figure H is a field picture of the adhesion measured by the peeling method, and Figure I is a field picture of the adhesion measured by the tensile method.

[0028] Figure 6 This is a graph showing the change in FITC fluorescence adhesion on the dorsum of rat tongue over time.

[0029] Figure 7 Figure 1 is a scanning electron micrograph of the copolymer p(MPA-co-APTAC-co-NA). Figure A is a scanning electron micrograph at a scale of 500 μm, and Figure B is a scanning electron micrograph at a scale of 300 μm.

[0030] Figure 8 Figure 1 is a graph showing the disintegration of the adhesive patch in 1 mL of artificial saliva over time. Figure A shows the disintegration of the adhesive patch in 1 mL of artificial saliva after 10 minutes, Figure B shows the disintegration of the adhesive patch in 1 mL of artificial saliva after 20 minutes, and Figure C shows the disintegration of the adhesive patch in 1 mL of artificial saliva after 30 minutes.

[0031] Fig. 9 Figure 1 is a diagram of the construction of the rat OLK model and the animal experiment scheme. Figure A is a picture of the tongue of a normal rat, Figure B is a picture of the hematoxylin-eosin (HE) staining of the tongue tissue of a normal rat, Figure C is a picture of the tongue of an OLK rat, and Figure D is a picture of the HE staining of the tongue tissue of an OLK rat.

[0032] Fig.10 HE staining images of the tongue dorsum mucosa and important organs of normal rats, with a scale bar of 200 μm. Figure A is a HE staining image of the tongue dorsum mucosa tissue of a normal rat without a patch attached, Figure B is a HE staining image of the tongue dorsum mucosa tissue of a normal rat with a patch attached for 1 day, Figure C is a HE staining image of the tongue dorsum mucosa tissue of a normal rat with a patch attached for 7 days, Figure D is a HE staining image of the heart tissue of a normal rat without a patch attached, Figure E is a HE staining image of the heart tissue of a normal rat with a patch attached for 1 day, Figure F is a HE staining image of the heart tissue of a normal rat with a patch attached for 7 days, Figure G is a HE staining image of the liver tissue of a normal rat without a patch attached, Figure H is a HE staining image of the liver tissue of a normal rat with a patch attached for 1 day, and Figure I is a HE staining image of the heart tissue of a normal rat with a patch attached for 7 days. Figure 1 is the HE staining picture of normal rat spleen tissue without patch adhesion, Figure K is the HE staining picture of normal rat spleen tissue with patch adhesion for 1 day, Figure L is the HE staining picture of normal rat spleen tissue with patch adhesion for 7 days, Figure M is the HE staining picture of normal rat lung tissue without patch adhesion, Figure N is the HE staining picture of normal rat lung tissue with patch adhesion for 1 day, Figure O is the HE staining picture of normal rat lung tissue with patch adhesion for 7 days, Figure P is the HE staining picture of normal rat kidney tissue without patch adhesion, Figure Q is the HE staining picture of normal rat kidney tissue with patch adhesion for 1 day, and Figure R is the HE staining picture of normal rat kidney tissue with patch adhesion for 7 days.

[0033] Fig.11 The following are the results of blood routine, serum biochemistry and electrolytes of normal rats before, 1 day and 7 days of adhesive patch treatment. Figure A is the result of red blood cell (RBC) counting, Figure B is the result of white blood cell (WBC) counting, Figure C is the result of hemoglobin (HGB) counting, Figure D is the result of platelet (PLT) counting, Figure E is the result of alanine aminotransferase (ALT), Figure F is the result of aspartate aminotransferase (AST), Figure G is the result of creatine kinase (CK), Figure H is the result of lactate dehydrogenase (LDH), Figure I is the result of creatinine (CREA), Figure J is the result of urea (UREA), and Figure K is the result of Ca 2+ The results of the measurement are shown in Figure L, which shows the Mg 2+ Measurement result diagram.

[0034] Fig.12 These are the images of OLK lesions on the dorsum of the tongue of rats in each group before treatment.

[0035] Fig.13 The following are the images of OLK lesions on the dorsum of the tongue of rats in each group at the end of treatment.

[0036] Fig.14Figure 1 is the statistical results of OLK lesions and body weight of rats in each group. Figure A is the tongue dorsum lesion score of rats in each group before and after treatment, Figure B is the tongue dorsum lesion score of rats in each group before and after treatment, Figure C is the statistical analysis result of tongue dorsum lesion area (≥50%, <50%) of rats in each group, and Figure D is the weight change of rats in each group. DETAILED DESCRIPTION

[0037] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.

[0038] JL01 ((4-(acryloyloxy)butyl)amino)(amino)methaniminium, 2,2,2-trifluoroacetate), TGA-NA (2-(2-(2-((3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethylacrylate), and TGA-CA (2-[2-(2-{[3-(2,4,6-trioxo-1,3,5-triazinan-1-yl)propanoyl]oxy}ethoxy)ethoxy]ethyl prop-2-enoate) are commercially available or can be synthesized by the following steps:

[0039] JL01: The compound tert-butyl N-[N'-(4-hydroxybutyl)-N-[(2-methylpropan-2-yl)oxycarbonyl]carbamimidoyl]carbamate is dissolved in dichloromethane, triethylamine and acryloyl chloride are added, and the mixture is stirred at room temperature for 3 to 10 hours to obtain an intermediate product. The intermediate product is purified by column chromatography, redissolved in dichloromethane, trifluoroacetic acid is added, and the mixture is reacted at room temperature for 0.5 to 2.5 hours to obtain the product.

[0040] TGA-NA: 2,6-diaminopurine is dissolved in DMSO, 2,6-di-tert-butyl-p-cresol and K2CO3 are added, and the mixture is stirred at 40-60°C for 0.5-2 h. Then, the compound 2-{2-[2-(buta-1,3-dien-2-yloxy)ethoxy]ethoxy}ethylprop-2-enoate is added to the reaction solution, and the mixture is stirred at 40-60°C for 12-24 h to obtain TGA-NA.

[0041] TGA-CA: Dissolve cyanuric acid in DMSO, add K2CO3, stir at 40-60℃ for 0.5-1 h, then add the compound 2-(2-{2-[(3-bromopropanoyl)oxy]ethoxy}ethoxy)ethylprop-2-enoate to the reaction solution, stir at room temperature for 12-24 h to obtain the product.

[0042] Example 1 A copolymer and a method for preparing the same

[0043] This embodiment provides a copolymer p(MPA-co-APTAC-co-NA) and a preparation method thereof, which comprises the following steps:

[0044] 2.7 mmol of methacrylamide (MPA), 2.7 mmol of (3-acrylamidopropyl)trimethylammonium chloride (APTAC), 0.6 mmol of base TGA-NA (IUPAC name: 2-(2-(2-((3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethyl acrylate) and 0.06 mmol of initiator 2,2′-azobis[2-(2-imidazoline-2-yl)propane)] dihydrochloride (VA-044) were added to a glass flask, 5 mL of pure water was added, ultrasonically dissolved and mixed, and then a magnetic stirrer was added and a rubber stopper was plugged. Then, the glass flask was evacuated with a vacuum pump and then filled with an argon bottle, and repeated 3 times to remove oxygen so that the reaction was carried out under argon conditions. Finally, the reaction mixture was reacted in an oil bath at 70 °C and 400 rpm for 2 hours. After the reaction, the mixture was cooled to room temperature and poured into a dialysis bag (molecular weight cutoff: 2000) for 3 days in pure water, with pure water replaced every 12 hours. After the dialysis, the liquid was freeze-dried to obtain a solid compound, which was then ground into a fine powder in a mortar. The powder storage conditions required vacuum drying.

[0045] In other embodiments, as shown in Tables 1-3, MPA can also be replaced by methacrylic acid (MAA) or 1-(methacryloyloxy)pyrrolidine-2,5-dione (MAPD); APTAC can also be replaced by guanidine (JL01) (IUPAC name: ((4-(acryloyloxy)butyl)amino)(amino)methaniminium, 2,2,2-trifluoroacetate); TGA-NA can also be replaced by TGA-CA (2-[2-(2-{[3-(2,4,6-trioxo-1,3,5-triazinan-1-yl)propanoyl]oxy}ethoxy)ethoxy]ethyl prop-2-enoate), and the synthesized copolymers are shown in Table 4.

[0046] Table 1 Names and structures of block A compounds

[0047]

[0048] Table 2 Names and structures of block B compounds

[0049]

[0050] Table 3 Names and structures of block C compounds

[0051]

[0052] Table 4 Name and structure of copolymers

[0053]

[0054]

[0055] Example 2 An oral mucosal adhesive patch and its preparation method

[0056] This embodiment provides an oral mucosal adhesive patch and a preparation method thereof, which comprises the following steps:

[0057] Single-layer patch: Figure 1 As shown, a polymer was prepared according to the method described in Example 1, and then 80 mg of polymer powder was weighed and pressed into tablets in a mold using a BJ15 manual infrared tablet press to obtain a rectangular patch of 10×15 mm in size and 500 μm in thickness. The pressed patch was white and opaque, with uniform particles, and was slightly light yellow after absorbing a small amount of water to form a gel. Patches of other shapes can also be prepared using molds of different shapes according to actual needs.

[0058] Double-layer patch: In order to be more suitable for the special complex environment of the oral cavity, which is highly dynamic and moist, a hydrophobic layer is added to one side of the adhesive patch to prepare a double-layer patch. The component of the hydrophobic layer is zein. Use a cotton swab to apply zein solution (4 g zein dissolved in 40 mL 75% ethanol) on the patch and place it in an oven to dry to form a zein hydrophobic layer.

[0059] Storage of the patch: After the patch is pressed into shape, place it in a vacuum desiccator for storage until needed.

[0060] The technical solution of the present invention is further described below through experiments. The copolymers used in the following experimental examples are prepared according to the method of Example 1, and the oral mucosal adhesive patches are prepared according to the method of Example 2.

[0061] Experimental Example 1 Determination of properties of copolymers

[0062] 1. Experimental Methods

[0063] The monomers and copolymers were 1 H NMR and UV-visible spectrophotometer.

[0064] 1 H NMR determination: 5-10 mg of MPA, APTAC, NA and copolymer p(MPA-co-APTAC-co-NA) were weighed, dissolved in deuterated dimethyl sulfoxide and placed in a nuclear magnetic resonance tube. The spectral characteristics were measured by AV II spectrometer at a frequency of 4600 MHz. 1 H NMR signal.

[0065] UV-visible spectrophotometer determination: 0.1 mg / mL aqueous solutions of MPA, APTAC, NA and copolymer p(MPA-co-APTAC-co-NA) were prepared respectively, and UV-vis signals were collected using a UV spectrophotometer (Agilent Cary Eclipse, USA) in the wavelength range of 210~340 nm.

[0066] 2. Experimental Results

[0067] 1 H NMR results are as follows Figure 2 Shown: Compared with MPA, APTAC and NA 1 Compared with the H NMR signal, the copolymer p(MPA-co-APTAC-co-NA) 1 In H NMR, there are no chemical shift signals of H on -CH3 and -CH2- of MPA, APTAC and NA, which confirms that p(MPA-co-APTAC-co-NA) is generated through the polymerization reaction. UV-vis results are as follows Figure 3As shown: the main characteristic peaks of p(MPA-co-APTAC-co-NA) are similar to those of NA.

[0068] The above results indicate that the copolymer p(MPA-co-APTAC-co-NA) was successfully synthesized in the present invention.

[0069] Experimental Example 2 Performance test of oral mucosal adhesive patch

[0070] 1. Experimental Methods

[0071] 1. Adhesion test

[0072] With the finger facing downward, one side of the single-layer adhesive patch is fixed on the finger, and the other side is used to adhere to the skin, buccal mucosa, lung, liver and heart tissues, etc., and the adhesion effect is observed.

[0073] 2. Determination of the Adhesion Force of Adhesive Patches Prepared from Copolymers with Different Monomer Ratios

[0074] Lap shear test method: In order to determine the oral adhesive wet adhesion performance of the patch, the lap shear test was used to test its adhesion to fresh porcine buccal mucosa. A single-layer powder patch with a standard size of 15×10×0.5 mm was made. Fresh porcine buccal mucosa was purchased from a local slaughterhouse. After fully moistening the surface of the porcine buccal mucosa with artificial saliva (Solarbio A7990) using a cotton swab, the patch was attached to the surface of the porcine buccal mucosa and lightly pressed with a 100 g weight for 30 s. The universal mechanical testing machine was used for measurement at a load of 50 N / min. The adhesion strength was calculated using the following formula: Adhesion strength = F max / S, where F max Maximum load, S is the adhesion area, the patch surface area is 150 mm 2 All tests were repeated at least three times and the results were expressed as mean ± standard deviation.

[0075] Tensile test method: A single-layer powder patch with a standard size of 15×10×0.5 mm was prepared. Fresh porcine buccal mucosa was purchased from a local slaughterhouse. The surface of the porcine buccal mucosa was fully moistened with artificial saliva using a cotton swab and then the patch was attached to the surface of the porcine buccal mucosa. A 100 g weight was used to press lightly for 30 s. The porcine buccal mucosa with the patch was fixed on the fixture and another piece of porcine buccal mucosa was attached to it. A force parallel to the surface of the patch was applied and the universal mechanical testing machine was used to measure at a load of 50 N / min until the patch fell off the porcine buccal mucosa.

[0076] Peel test method: A single-layer powder patch of standard size 15×10×0.5 mm was prepared. Fresh porcine buccal mucosa was purchased from a local slaughterhouse. The surface of the porcine buccal mucosa was fully moistened with artificial saliva using a cotton swab and then the patch was attached to the surface of the porcine buccal mucosa. A 100 g weight was used to press lightly for 30 s. The porcine buccal mucosa with the patch was fixed on the fixture and another piece of porcine buccal mucosa was attached parallel to it. A force perpendicular to the surface of the patch was applied and the universal mechanical testing machine was used to measure at a load of 50 N / min until the patch fell off the porcine buccal mucosa.

[0077] In order to screen the optimal monomer ratio, the overlap shear test method was used for optimization experiments. First, the TGA-NA ratios of 5%, 10%, and 15% (the molar ratio of MPA and APTAC was 1:1) were used for polymerization reaction, and the adhesion of the prepared adhesive patch was measured to determine the optimal molar ratio of TGA-NA. Then, the content of TGA-NA was fixed to explore the adhesion of the adhesive patch prepared under different molar ratios of MPA and APTAC. The molar ratios of MPA and APTAC were 3:1, 2:1, 1:1, 1:2, and 1:3, respectively.

[0078] 3. Determination of the adhesion of oral mucosal adhesive patches to wet and dry surfaces

[0079] The single-layer adhesive patch prepared under the optimal monomer molar ratio was used to measure the adhesion of the wet and dry porcine buccal mucosa surfaces by lap shear test. The porcine buccal mucosa was purchased fresh from a local slaughterhouse. The surface of the porcine buccal mucosa was fully moistened with artificial saliva dipped in a cotton swab, which was the wet porcine buccal mucosa surface; the surface of the porcine buccal mucosa was wiped dry with a medical cotton swab and absorbent paper, which was the dry porcine buccal mucosa surface.

[0080] 4. Determination of the adhesion force of oral mucosal adhesive patches under different pressures

[0081] The single-layer adhesive patch prepared at the optimal monomer molar ratio was used to measure the adhesion of the adhesive patch to fresh porcine buccal mucosa under different pressures (0.25N, 0.5N, 1N, and 2N) using the lap shear test method.

[0082] 5. Determination of adhesion of different oral adhesive patches and drugs

[0083] The adhesion of different oral adhesive patches to fresh porcine buccal mucosa was determined by lap shear test. The oral adhesive patches were the single-layer adhesive patch prepared by the present invention (monomer ratio was 45%:45%:10%), commercially available Zizhu ulcer membrane, and tretinoin cream.

[0084] 6. Determination of in vivo adhesion time

[0085] Before the experiment, 6-8 week old SD rats were fasted overnight and had free access to water. They were anesthetized with 10% chloral hydrate 350-400 mg / kg intraperitoneally and randomly divided into four groups. The rats were applied with 1% FITC aqueous solution, 1% FITC labeled retinoic acid cream, 1% FITC labeled single-layer patch, and 1% FITC labeled double-layer patch on the tongue dorsum, respectively. At specific time intervals, the fluorescence intensity of the tongue dorsum of each group was observed and recorded to reflect the wet adhesion ability of the patch in vivo.

[0086] 7. Determination of microscopic morphology

[0087] The polymer p(MPA-co-APTAC-co-NA) was absorbed by water to form a gel and then freeze-dried, and its microscopic morphology was observed using a scanning electron microscope.

[0088] 8. Determination of pH and disintegration

[0089] After absorbing water on the surface of the adhesive patch, the pH was measured using a pH meter (inoLabpH7310).

[0090] After the adhesive patch absorbed water and turned into gel, the weight was measured and the disintegration of the patch in 1 mL and 50 mL of artificial saliva was observed.

[0091] 2. Experimental Results

[0092] 1. Adhesion of adhesive patches prepared from copolymers with different monomer ratios

[0093] The results of adhesion test are as follows Figure 4 As shown in the figure, the p(MPA-co-APTAC-co-NA) patch has good adhesion to skin, buccal mucosa, lung, liver and heart tissues. The adhesion results of the screening experiment are shown in the figure. Figure 5 As shown in A, B and Table 5: the adhesion force of the adhesive patch containing 5% TGA-NA was 30.73±0.91 kPa, the adhesion force of the adhesive patch containing 10% TGA-NA was 65.64±4.67 kPa, and the adhesion force of the adhesive patch containing 15% TGA-NA was 30.73±0.91 kPa, indicating that the optimal molar content of TGA-NA is 10%. When the ratio of MPA:APTAC decreased from 3:1, 2:1 to 1:1, the adhesion of the adhesive patch gradually increased, and was 26.54±9.54 kPa, 37.71±8.03 kPa, and 65.64±4.67 kPa, respectively. When the content of APTAC increased further, the adhesion decreased, that is, when the ratio of MPA:APTAC was 1:2 and 1:3, the adhesion was 14.79±3.35 kPa and 10.32±2.44 kPa, respectively. Therefore, when used for adhesive patches, the optimal molar ratio of each block monomer MPA, APTAC, and TGA-NA is 45%:45%:10%.

[0094] Table 5 Relationship between different monomer molar ratios and wet adhesion

[0095]

[0096] Adhesion results on wet and dry surfaces are as follows Figure 5 As shown in Figure C: The adhesive patch prepared at the optimal molar ratio has an adhesion force of 65.64±4.67 kPa to the moist porcine buccal mucosa and an adhesion force of 44.33±6.64 kPa to the dry porcine buccal mucosa surface. The adhesion force of the adhesive patch to the moist porcine buccal mucosa is significantly greater than that to the dry porcine buccal mucosa surface, which confirms that the patch is suitable for the moist environment of the oral mucosa, indicating the importance of hydration for patch adhesion. The adhesion results of the patch under different pressures are shown in Figure 2. Figure 5 As shown in D: When the pressure is 0.25 N, the adhesion force is 7.31±3.00 kPa, when the pressure is 0.5 N, the adhesion force is 9.98±4.23 kPa, and when the pressure increases to 1 N and 2 N, the adhesion force is 20.79±3.46 kPa and 19.82±2.89 kPa, respectively. This shows that as the pressure increases, the wet adhesion of the adhesive patch increases.

[0097] Adhesion results of different oral patches are as follows Figure 5 As shown in E: Under the same conditions, the wet adhesion of commercially available oral patches was tested by lap shear test. The adhesion of Zizhu ulcer membrane was only 4.30±0.58 kPa, and the adhesion of retinoic acid cream was 1.20±0.36 kPa, indicating that the patch prepared by the present invention has better wet adhesion than the commercially available oral patches. The results of the tensile test and the peeling test are shown in Figure 5 As shown in FI: the adhesion forces measured by the two detection methods were 13.51±3.51 kPa and 5.44±1.43 kPa, respectively, both of which were smaller than the adhesion force in the lap shear test, which more comprehensively characterized the adhesion force of the adhesive patch on the pig buccal mucosa.

[0098] The above results show that the optimal molar ratio of each block monomer MPA, APTAC and NA is 45%:45%:10%. The adhesive patch prepared under the optimal ratio has a good adhesion effect on various tissues of the organism, is more suitable for the moist environment of the oral mucosa, and has a greater adhesion force than commercially available oral patches.

[0099] 2. In vivo adhesion time

[0100] The results of in vivo adhesion experiments were Figure 6As shown in the figure: the fluorescence of the group with 1% FITC aqueous solution applied to the tongue dorsum mucosa disappeared after 4 hours, the fluorescence of the group with 1% FITC labeled retinoic acid cream lasted for about 6 hours, the group with 1% FITC labeled single-layer patch still had strong green fluorescence after 8 hours, and the green fluorescence duration of the group with 1% FITC labeled double-layer patch was further extended to 10 hours. This shows that the adhesive patch prepared by the present invention can maintain long-term adhesion when used on the tongue in the oral cavity, and the double-layer adhesive patch can maintain adhesion for at least 10 hours, which is significantly longer than the drug molecule.

[0101] 3. Microscopic morphology

[0102] The scanning electron microscopy results are as follows Figure 7 As shown: The microstructure of polymer p(MPA-co-APTAC-co-NA) is porous, which is conducive to drug loading.

[0103] 4. pH and disintegration

[0104] After the adhesive patch surface absorbs water, the pH value is 7.5-8.0, which is close to neutral and has no obvious irritation to the oral mucosa. Figure 8 As shown: After the adhesive patch absorbs water to form a gel, the initial weight is about 100 mg. After 10 minutes in 50 mL of artificial saliva, the patch completely disintegrates. In 1 mL of artificial saliva, the patch partially disintegrates after 20 minutes, and almost completely disintegrates after 30 minutes, confirming that the patch gradually swells and disintegrates after contact with saliva during oral application.

[0105] The above results show that the present invention selects the best monomer ratio through screening tests, and the prepared adhesive patch has good mucosal wet adhesion performance, better adhesion than commercially available oral patches, and better in vivo adhesion time than drug molecules. After the adhesive patch absorbs water, the porous structure is conducive to carrying drugs, and the neutral patch surface has no obvious stimulation to oral adhesion. In the oral saliva environment, the adhesive patch will gradually disintegrate, indicating that the adhesive patch of the present invention is suitable for the special environment of the oral cavity that is highly dynamic and moist.

[0106] Experimental Example 3 Application of oral mucosal adhesive patch in the treatment of oral leukoplakia

[0107] 1. Experimental Methods

[0108] 1. Biocompatibility test

[0109] SD rats were randomly divided into a blank control group and a p(MPA-co-APTAC-co-NA) patch group. In the p(MPA-co-APTAC-co-NA) patch group, a double-layer p(MPA-co-APTAC-co-NA) patch was applied to the dorsal mucosa of the rat tongue, and the rats were killed on the first and seventh days, respectively, and the tongue, heart, liver, spleen, lung, and kidney were obtained for HE staining, and blood was collected from the eyeball for routine blood tests and hematological tests.

[0110] 2. Tissue HE staining experiment

[0111] SD rats were randomly divided into a blank control group and a double-layer adhesive patch group. The double-layer adhesive patch was attached to the dorsal mucosa of the rat tongue. The rats were killed on the 1st and 7th days, respectively, and the tongue, heart, liver, spleen, lung and kidney were obtained for HE staining.

[0112] HE staining method: ① Place the paraffin sections in a 65 ℃ constant temperature oven and bake for 2 h; ② Dewax and hydrate the paraffin sections in sequence (dewax in xylene I and II solutions for 15 min each, and hydrate in 100% I, 100% II, 95%, 80%, and 75% gradient alcohol for 5 min each); ③ Rinse with distilled water 3 times, 5 min / time; ④ Stain with hematoxylin for 1 min, differentiate with 1% hydrochloric acid alcohol for 3-5 s, and reverse blue with running water for 15 min; ⑤ Counterstain with eosin for 1-2 min, rinse with tap water for 30 s; ⑥ Dehydrate in 80%, 90%, and 100% gradient alcohol for 5 min each; ⑦ Transparent in xylene I and II solutions, and seal with neutral gum.

[0113] 3. Rat hematology test experiment

[0114] SD rats were randomly divided into a blank control group and a double-layer adhesive patch group. The double-layer adhesive patch was applied to the dorsal mucosa of the rat tongue. Blood was collected from the eyeball on the first and seventh days for routine blood tests, serum biochemical tests, and electrolyte tests. Routine blood tests included red blood cell, white blood cell, hemoglobin, and platelet counts. Serum biochemical tests included liver function indicators: alanine aminotransferase (ALT), aspartate aminotransferase (AST), myocardial enzyme indicators: creatine kinase (CK), lactate dehydrogenase (LDH), renal function indicators: urea (UREA) and creatinine (CREA), and electrolyte tests included Ca 2+ Mg 2+ .

[0115] 4. Construction of OLK model animals

[0116] like Fig. 9As shown: 6-8 week old SD rats were induced to drink 75 μg / mL 4-nitroquinoline N-oxide (4-NQO) solution by drinking water. The 4-NQO solution was changed three times a week to ensure the freshness and effectiveness of 4-NQO. As the drinking time increased, the dorsal mucosa of the rat tongue gradually changed from the original smooth pink to white, rough until white spots formed. At the 16th week, three rat tongues were randomly selected for HE staining to verify the successful construction of the OLK model animal. The control group was given sterile drinking water at the same time.

[0117] 4. Determination of animal tongue lesions

[0118] OLK rats were randomly divided into 4 groups, namely, blank control PBS group (n=7), tretinoin cream group (n=8), double-layer adhesive patch group (n=7) and double-layer adhesive patch group with tretinoin (n=8). Each group of rats received treatment once a day (PBS solution, tretinoin, and local patch application on the tongue dorsum) for 4 consecutive weeks. The rats were weighed every week and photographed to record the lesions on the tongue dorsum of the rats.

[0119] 5. Quantitative scoring method for tongue lesions

[0120] The tongue lesions were scored in terms of size, type, and color to quantify the treatment effect according to the following method: ① Area size: Compared with before treatment, a decrease of ≥50% in the cross-sectional area of ​​the measurable white spot was scored as negative 2 points, an increase of ≥50% was scored as 2 points, and the rest was scored as 0 points. ② Lesion type: It was mainly divided into three levels based on the surface roughness, degree of protrusion, ulceration or erosion: granular protrusions, warty protrusions, villous protrusions or thorny protrusions that were significantly higher than the mucosal surface or had ulcers were scored as 3 points; uneven and higher than the mucosal surface, with local ulcers, scored as 2 points; homogeneous plaques slightly higher than the mucosal surface, without ulcers, scored as 1 point. ③ Color was divided into two levels, pure self-color was scored as 2 points, and gray or light self-color was scored as 1 point. The treatment effect was evaluated and scored independently by two experienced oral mucosa clinicians.

[0121] 2. Experimental Results

[0122] 1. Biocompatibility of adhesive patches

[0123] Good biocompatibility is the basic requirement for the application of adhesive patches in living bodies. Visual observation showed that the adhesive patch had no irritation to the tongue dorsum mucosa of rats, and the color, shape and texture of the tongue dorsum were normal after local application. Fig.10 As shown in the figure, the mucosa of the adhesive patch group and the blank control group were consistent, no inflammatory reaction was observed in the tissue, and the cell morphology was normal. Fig.11As shown: blood routine, serum biochemical indexes and electrolyte tests were normal. The above results show that the adhesive patch of the present invention has good biocompatibility, no obvious irritation and toxicity, and has the potential to be used in vivo to treat diseases.

[0124] 2. Adhesive patches are used to treat oral leukoplakia

[0125] The OLK lesions on the dorsum of the tongue before treatment in each group were as follows Fig.12 As shown in the figure, during the treatment, except for the group with retinoic acid adhesive patch, no rats died, while one rat died in each of the other three groups. Fig.13 As shown: the tongue dorsum lesions in the PBS group were more obvious than those in the other three groups. Three rats in the PBS group had obvious growths and ulcers at the tongue root. The tongue lesions in the retinoic acid-loaded adhesive patch group were significantly lighter in color and less rough, indicating that the retinoic acid-loaded adhesive patch was more effective in treating OLK. When loaded with retinoic acid, the long-term in vivo adhesion of the adhesive patch is conducive to prolonging the retention time of the loaded drug in the oral mucosa, and achieving sustained and slow release of the drug locally in the oral mucosa.

[0126] The lesion score results are as follows Fig.14 As shown in A and B: There was no significant difference in the scores of each group before treatment. At the end of treatment, compared with the PBS group and the adhesive patch group, the lesion scores of the topical application group of tretinoin cream and the tretinoin-loaded adhesive patch group were significantly lower, and the difference was statistically significant. Although the lesion scores of each group increased at the end of treatment compared with before treatment, the increase in the tretinoin-loaded adhesive patch group was the smallest. Fig.14 As shown in C: In the PBS control group, 4 rats had tongue dorsum lesion area (including keratinization, white lesions, cancerous ulcers, and growths) ≥ 50%, while in the retinoic acid cream group, 2 rats, in the adhesive patch group, 3 rats, and in the retinoic acid adhesive patch group, only 1 rat had tongue dorsum lesion area (including keratinization, white lesions, cancerous ulcers, and growths) ≥ 50%. Fig.14 As shown in D: During the treatment, the body weight of rats in each group decreased slightly, and the weight loss of the retinoic acid adhesive patch group was the least. The above results confirmed that compared with the blank control and retinoic acid cream groups, the retinoic acid adhesive patch group had a better OLK treatment effect.

[0127] The above results show that the adhesive patch prepared by the present invention has good biocompatibility, and when used to treat rat OLK, the drug-loaded adhesive patch can significantly alleviate the lesions of the tongue. Compared with the treatment of applying the drug alone or the adhesive patch alone, the drug-loaded adhesive patch can achieve a more effective treatment effect.

[0128] Through the above embodiments and experimental examples, it can be seen that the present invention provides a polymer-based oral mucosal adhesive patch and its preparation method and use. The present invention uses methacrylic acid / methacrylamide / 1-(methacryloyloxy)pyrrolidine-2,5-diketone, (3-acrylamidopropyl)trimethylammonium chloride / guanidine, and base / cyanuric acid derivatives as basic building units, synthesizes 12 copolymers by free radical polymerization, and forms 12 oral adhesive patches with different compositions by tableting the polymer powder. The adhesive patch has good mucosal wet adhesion performance, better adhesion than commercially available oral patches, and longer adhesion time in vivo than drug molecules. In addition, the porous structure of the adhesive patch is conducive to drug loading, and the neutral patch surface has no obvious stimulation to oral adhesion. In the oral saliva environment, the adhesive patch will gradually disintegrate, indicating that the adhesive patch of the present invention is suitable for the highly dynamic and moist special environment of the oral cavity. The adhesive patch has good biocompatibility. When used to treat rat OLK, the loaded drug can significantly alleviate the lesions of the tongue. Compared with applying drugs alone or applying adhesive patches alone, drug-loaded adhesive patches can achieve more effective treatment effects and meet the needs of treating oral mucosal diseases. Furthermore, the drugs delivered by the adhesive patch through the oral mucosa can also enter the systemic blood circulation through the oral submucosal blood vessels, thereby improving the bioavailability of the drugs and achieving efficient treatment of systemic diseases.

Claims

1. A polymer, characterized in that The preparation is carried out according to the following steps: block A, block B and block C are mixed and reacted to obtain the product; The block A is selected from one or a combination of at least two of methacrylic acid, methacrylamide, and 1-(methacryloyloxy)pyrrolidine-2,5-dione; the block B is selected from at least one of (3-acrylamidopropyl)trimethylammonium chloride and ((4-(acryloyloxy)butyl)amino)(amino)methaniminium, 2,2,2-trifluoroacetate; the block C is selected from 2-(2-(2-((3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethylacrylate, At least one of 2-[2-(2-{[3-(2,4,6-trioxo-1,3,5-triazinan-1-yl)propanoyl]oxy}ethoxy)ethoxy]ethyl prop-2-enoate; The molar content ratio of the block A, block B and block C is 21.25%-71.25%: 21.25%-71.25%: 5%-15%; ((4-(acryloyloxy)butyl)amino)(amino)methaniminium, The chemical structural formula of 2,2,2-trifluoroacetate is as follows: The chemical structural formula of 2-(2-(2-((3-(2,6-diamino-9H-purin-9-yl)propanoyl)oxy)ethoxy)ethoxy)ethylacrylate is the following formula II, The chemical structural formula of 2-[2-(2-{[3-(2,4,6-trioxo-1,3,5-triazinan-1-yl)propanoyl]oxy}ethoxy)ethoxy]ethyl prop-2-enoate is the following formula III, 2. The polymer according to claim 1, characterized in that: The molar content ratio of the block A, block B and block C is 45%:45%:10%.

3. The polymer according to claim 1, characterized in that: The mixing is mixing block A, block B, block C and initiator; The initiator is selected from 2,2′-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride and N,N-diisopropylethylamine.

4. The polymer according to claim 1, characterized in that: The mixed solvent is selected from water and dichloromethane; and / or the reaction temperature is 65-70° C.; and / or the reaction speed is 400-500 rpm; and / or the reaction time is 1.5-2 hours.

5. The method for preparing the polymer according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing block A, block B and block C and reacting them to obtain the product.

6. Use of the polymer according to any one of claims 1 to 4, characterized in that: Use as a drug carrier in preparing drugs and / or wet adhesives and / or preparing medical patches.

7. An oral mucosal adhesive patch, characterized in that: The preparation is carried out according to the following steps: the polymer described in any one of claims 1 to 4 is pressed into tablets to obtain the product.

8. The oral mucosal adhesive patch according to claim 7, characterized in that: After the polymer is pressed into a sheet, a hydrophobic layer is added to one side of the sheet to obtain the sheet.

9. The method for preparing the oral mucosal adhesive patch according to any one of claims 7 and 8, characterized in that: The method comprises the following steps: pressing the polymer described in any one of claims 1 to 4 into sheets.

10. Use of the oral mucosal adhesive patch according to any one of claims 7 and 8, characterized in that: Use as a drug carrier in the preparation of drugs; And / or, use in preparing materials for treating oral mucosal diseases or tissue repair materials.

Citation Information

Patent Citations

  • Mucoadhesive gel composition

    CN113164384A

  • Mucous membrane adhesive material with single-sided biological adhesion and preparation method thereof

    CN115444812A